2019
DOI: 10.1002/zaac.201900279
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Five‐Fold Interpenetrating Framework with the dmc Topology that is Supported by Extensive O–H···O Hydrogen Bonds

Abstract: A unique supramolecular framework, [Zn 4 (H 2 O) 2 (2,5tdc) 4 (3,3Ј-bpe) 3 ] n (1), was prepared by the self-assembly of Zn(NO 3 ) 2 ·6H 2 O, 2,5-thiophenedicarboxylic acid (2,5-H 2 tdc), and 1,2-bis(3-pyridyl)-ethene (3,3Ј-bpe) under hydrothermal conditions. The coordination network of 1 can be simplified as a (3,4)-connected dmc framework with a point symbol (4·8 2 )(4·8 5 ). The void space of a single network of 1 is filled by mutual interpenetration of four crystallographically equivalent nets, generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[6][7][8] By referring a large amount of literatures about MOFs, it is found that selection of an suitable organic ligand and adopt a appropriate synthetic strategy can help us to construct the desired MOFs to some extent. [9][10][11][12] In the construction of MOFs, polycarboxylate ligands with versatile coordination modes have been widely used as the organic building blocks, [13][14][15] and the mixed-ligand strategy has been proven to be one of the most effective methods for the construction MOFs with desired structures. [16][17][18] The synergestic effect of two different ligands can help us to direct the synthesis of desired MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] By referring a large amount of literatures about MOFs, it is found that selection of an suitable organic ligand and adopt a appropriate synthetic strategy can help us to construct the desired MOFs to some extent. [9][10][11][12] In the construction of MOFs, polycarboxylate ligands with versatile coordination modes have been widely used as the organic building blocks, [13][14][15] and the mixed-ligand strategy has been proven to be one of the most effective methods for the construction MOFs with desired structures. [16][17][18] The synergestic effect of two different ligands can help us to direct the synthesis of desired MOFs.…”
Section: Introductionmentioning
confidence: 99%